Phosphate Solubilizing Microorganisms 2014
DOI: 10.1007/978-3-319-08216-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Consortium of Plant Growth-Promoting Rhizobacteria Improves the Performance of Plants Growing in Stressed Soils: An Overview

Abstract: Soil and associated stress conditions not only influence dwelling microbial populations and soil ecosystems but also affect growth and yield of plants. Major soil stress includes salinity, drought, and metal contamination. Due to burgeoning populations and expanding food demands, it has become imperative to alleviate the stressful soil conditions so that the crop production is increased and, consequently, the food demands are fulfilled. Different strategies are followed to resolve this problem, and one such ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 141 publications
2
8
0
Order By: Relevance
“…Phosphate solubilization is another important trait of PGPR and the isolates of the current study revealed a significant release of PO 4 3- from insoluble complex TCP. The findings of the current study are in agreement with numerous published literatures reporting solubilization of phosphate by Bacillus, Pseudomonas , and Azotobacter (Ahmad et al, 2008; Bhattacharyya and Jha, 2012; Panwar et al, 2014; Maitra et al, 2015). Besides providing phosphorous to the plants, the PSBs also enhance the plant’s growth by stimulating nitrogen fixation, enhancing availability of trace metals and by formation of plant growth hormones (Kumar et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Phosphate solubilization is another important trait of PGPR and the isolates of the current study revealed a significant release of PO 4 3- from insoluble complex TCP. The findings of the current study are in agreement with numerous published literatures reporting solubilization of phosphate by Bacillus, Pseudomonas , and Azotobacter (Ahmad et al, 2008; Bhattacharyya and Jha, 2012; Panwar et al, 2014; Maitra et al, 2015). Besides providing phosphorous to the plants, the PSBs also enhance the plant’s growth by stimulating nitrogen fixation, enhancing availability of trace metals and by formation of plant growth hormones (Kumar et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…To enhance the beneficial functions displayed by these bacteria, the design of bacterial consortia has gained interest as a suitable strategy for sustainable food production. A bacterial consortium generally constitutes two or more compatible bacteria of different species in a synergistic or additive interaction [42][43][44]. In some cases, a mixture of different strains of the same species can exhibit enhanced activities and also be considered a consortium.…”
Section: Bacterial Consortiamentioning
confidence: 99%
“…12 In general, it has been reported by several researchers that inoculation with consortia have better plant growth promotion as compared to individual inoculations because individual strain is supplementing to each other for their beneficial traits. 13,14 We have used 2 well proven PGPR Pseudomonas putida NBRIRA (RA) and Bacillus amyloliquefaciens NBRISN13 (SN13) in our laboratory. 15,16 The strain RA is Gram negative and displayed multiple PGP activities like auxin production, phosphate solubilisation and tolerance to drought and salt stresses.…”
Section: Introductionmentioning
confidence: 99%